Chronic administration of prebiotics and probiotics ameliorates pathophysiological hallmarks of Alzheimer’s disease in a APP/PS1 transgenic mouse model - Lana, Daniele; Traini, Chiara; Bulli, Irene; Sarti, Giorgia; Magni, Giada; Attorre, Selene; Giovannini, Maria Grazia; Vannucchi, Maria Giuliana (Frontiers in Pharmacology, 2024)
The gut microbiota (MB), although one of the main producers of Aβ in the body, in physiological conditions contributes to the maintainance of a healthy brain. Dysbiosis, the dysbalance between Gram-negative and Gram-positive bacteria in the MB increases Aβ production, contributing to the accumulation of Aβ plaques in the brain, the main histopathological hallmark of Alzheimer’s disease (AD). Administration of prebiotics and probiotics, maintaining or recovering gut-MB composition, could represent a nutraceutical strategy to prevent or reduce AD sympthomathology. Aim of this research was to evaluate whether treatment with pre- and probiotics could modify the histopathological signs of neurodegeneration in hippocampal CA1 and CA3 areas of a transgenic mouse model of AD (APP/PS1 mice). The hippocampus is one of the brain regions involved in AD. Tg mice and Wt littermates (Wt-T and Tg-T) were fed daily for 6 months from 2 months of age with a diet supplemented with prebiotics (a multi-extract of fibers and plant complexes, containing inulin/fruit-oligosaccharides) and probiotics (a 50%-50% mixture of Lactobacillus rhamnosus and Lactobacillus paracasei). Controls were Wt and Tg mice fed with a standard diet. Brain sections were immunostained for Aβ plaques, neurons, astrocytes, microglia, and inflammatory proteins that were evaluated qualitatively and quantitatively by immunofluorescence, confocal microscopy and digital imaging with Image J software. Quantitative analyses demonstrated that: 1) The treatment with pre- and probiotics significantly decreased Aβ plaques in CA3, while in CA1 the reduction was not significant; 2) Neuronal damage in CA1 Stratum Pyramidalis was significantly prevented in Tg-T mice; no damage was found in CA3; 3) In both CA1 and CA3 the treatment significantly increased astrocytes density, and GFAP and IBA1 expression, especially around plaques; 4) microglia reacted differently in CA1 and CA3: in CA3 of Tg-T mice there was a significant increase of CD68+ phagocytic microglia (ball-and-chain phenomic) and of CX3CR1 compared with CA1. The higher microglia reactivity could be responsible for their more efficient scavenging activity towards Aβ plaques in CA3 in comparison to CA1. Treatment with pre- and probiotics, modifying many of the physiopathological hallmarks of AD, could be considered an effective nutraceutical strategy against AD symptomatology.